Human trafficking, human misery : the global trade in human beings - Aronowitz, Alexix A. (Libros electrónicos en Ebscohost, 2009)
Virtually all countries in the world are affected by the scourge of human trafficking, either as a source, transit, or destination country, or combination thereof.